The Effect of Self-Regulated Learning on Continuous Upright Writing Skills Elementary School Students - Agustina, Erpin; Winarni, Retno; Santosa, Eka Budhi (Universitas Sebelas Maret, 2026)
Continuous upright writing (menulis tegak bersambung) is a fundamental literacy skill that requires fine motor coordination and cognitive self-regulation, yet individual differences in students’ ability to manage their own learning processes may account for variations in writing quality. This study aims to analyze the influence of self-regulated learning on the continuous upright writing skills of 4th grade elementary school students in Wonogiri Regency. The research uses an Ex Post Facto method with a correlational design. The research population is grade 4 students from 5 elementary schools in Wonogiri with a total sample of 78 students selected by purposive sampling. The research instrument used a self-regulated learning questionnaire adapted from the Zimmerman model and a continuous upright writing skill test which was assessed based on the aspects of readability, letter shape accuracy, and fluency. Data analysis used product moment correlation test and simple linear regression. The results showed a significant positive correlation between self-regulated learning and continuous upright writing skills (r = 0.687; p < 0.01). Regression analysis showed that self-regulated learning contributed 47.2% to the variation in continuous upright writing skills. Students with high levels of self-regulated learning have better continuous upright writing skills than students with low levels of self-regulated learning. This study emphasizes the importance of developing self-regulated learning skills as a strategy to improve the continuous upright writing skills of elementary school students.